2021
DOI: 10.1002/mds.28890
|View full text |Cite
|
Sign up to set email alerts
|

Mild Chronic Colitis Triggers Parkinsonism in LRRK2 Mutant Mice Through Activating TNF‐α Pathway

Abstract: Background Leucine‐rich repeat kinase 2 (LRRK2) is a common risk gene for Parkinson's disease (PD) and inflammatory bowel disorders. However, the penetrance of the most prevalent LRRK2 mutation, G2019S, is <50%. Factors other than genetic mutations are needed in PD process. Objectives To examine whether and how gut inflammation may act as an environmental trigger to neurodegeneration in PD. Methods A mild and chronic dextran sodium sulfate (DSS)‐induced colitis mice model harboring LRRK2 G2019S mutation was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 56 publications
(103 reference statements)
3
21
0
Order By: Relevance
“…Among subjects with PD, the number of LRRK2-positive cells was higher in those with the LRRK2 genetic risk variants G2385R and R1628P compared with those without LRRK2 mutations. 1 The authors summarize their findings by stating, "Our findings from human participants are supportive of the observations from the LRRK2 G2019S chronic colitis mice." 1 Although we agree with the authors that their findings obtained in human samples are potentially interesting, we would like to draw their attention to a recently published article by our group 2 in which we analyzed LRRK2 expression in the human gastrointestinal tract.…”
Section: Mild Chronic Colitis Triggers Parkinsonism In Lrrk2 Mutant M...mentioning
confidence: 59%
See 4 more Smart Citations
“…Among subjects with PD, the number of LRRK2-positive cells was higher in those with the LRRK2 genetic risk variants G2385R and R1628P compared with those without LRRK2 mutations. 1 The authors summarize their findings by stating, "Our findings from human participants are supportive of the observations from the LRRK2 G2019S chronic colitis mice." 1 Although we agree with the authors that their findings obtained in human samples are potentially interesting, we would like to draw their attention to a recently published article by our group 2 in which we analyzed LRRK2 expression in the human gastrointestinal tract.…”
Section: Mild Chronic Colitis Triggers Parkinsonism In Lrrk2 Mutant M...mentioning
confidence: 59%
“…1 The authors summarize their findings by stating, "Our findings from human participants are supportive of the observations from the LRRK2 G2019S chronic colitis mice." 1 Although we agree with the authors that their findings obtained in human samples are potentially interesting, we would like to draw their attention to a recently published article by our group 2 in which we analyzed LRRK2 expression in the human gastrointestinal tract. In keeping with previous findings obtained in mice, 2 we first showed that the distribution of LRRK2 in the human gastrointestinal tract was not limited to the immune cells but also extended to the two main plexuses of the human enteric nervous system, namely, the submucosal and myenteric plexus 3 (Fig.…”
Section: Mild Chronic Colitis Triggers Parkinsonism In Lrrk2 Mutant M...mentioning
confidence: 59%
See 3 more Smart Citations